Molecular modelling and dynamic simulations of sequestosome 1 (SQSTM1) missense mutations linked to Paget disease of bone. Issue 8 (24th May 2021) - Shaik, Noor Ahmad; Nasser, Khalidah K.; Alruwaili, Muteb Muidh; Alallasi, Sami Raja; Elango, Ramu; Banaganapalli, Babajan
Abstract: The Paget disease (PDB; OMIM is 167250) is a chronic bone disease caused by pathogenic mutations in Sequestome1/p62 (SQSTM1) gene. This study has aimed to interpret the relationship of PDB linked SQSTM1 mutations with protein structure and its molecular dynamic features. The disease causative missense mutations were initially collected, and then analyzed for their, exonic and domain distribution, impact on secondary and tertiary structures, and their ability on protein-ligand interactions, using a combination of systems biology approaches. Our results show that most PDB linked SQSTM1 missense mutations affect amino acid residues clustered within or near the UBA domain (aa 389–434), which participates in the ubiquitination of substrates. We also report that the majority mutations occurred in α-helices over β-strands but their effects on the secondary structure were mostly neutral. Global tertiary structure deviations were minimal; however, at amino acid residue level minor structural changes were evident. The molecular dynamics simulation analysis showed that both PB1 and UBA domains were under constant structural fluctuations resulting in closed form conformation of SQSMT1 protein structure, when it is bound to PRKCI ligand. We also found salt bridge conformation changes in the UBA domain of SQSTM1 mutants when they bound to the PRKCI interactor protein. This finding suggests the possibility that mutations in SQSTM1 could impair its ability to ubiquitinate the substrates, eventually affecting autophagy and apoptosis, especially in mature osteoclasts. This study presents the additional insight into structure and function relationship between SQSTM1 mutations and PDB pathogenesis. Communicated by Ramaswamy H. Sarma.